Triassic to Early Jurassic (c. 200 Ma) UHP metamorphism in the Central Rhodopes: evidence from U–Pb–Th dating of monazite in diamond‐bearing gneiss from Chepelare (Bulgaria). (10th February 2016) - Petrík, I.; Janák, M.; Froitzheim, N.; Georgiev, N.; Yoshida, K.; Sasinková, V.; Konečný, P.; Milovská, S.
Abstract: Evidence for ultrahigh‐pressure metamorphism (UHPM) in the Rhodope metamorphic complex comes from occurrence of diamond in pelitic gneisses, variably overprinted by granulite facies metamorphism, known from several areas of the Rhodopes. However, tectonic setting and timing of UHPM are not interpreted unanimously. Linking age to a metamorphic stage is a prerequisite for reconstruction of these processes. Here, we use monazite in diamond‐bearing gneiss from Chepelare (Bulgaria) to date the diamond‐forming UHPM event in the Central Rhodopes. The diamond‐bearing gneiss comes from a strongly deformed, lithologically heterogeneous zone (Chepelare Mélange) sandwiched between two migmatized orthogneiss units, known as Arda‐I and Arda‐II. Diamond, identified by Raman micro‐spectroscopy, shows the characteristic band mostly centred between 1332 and 1330 cm −1 . The microdiamond occurs as single grains or polyphase diamond + carbonate inclusions, rarely with CO2 . Thermodynamic modelling shows that garnet was stable at UHP conditions of 3.5–4.6 GPa and 700–800 °C, in the stability field of diamond, and was re‐equilibrated at granulite facies/partial melting conditions of 0.8–1.2 GPa and 750–800 °C. The texture of monazite shows older central parts and extensive younger domains which formed due to metasomatic replacement in solid residue and/or overgrowth in melt domains. The monazite core compositions, with distinctly lower Y, Th and U contents, suggest its formation in equilibrium with garnet. The U–Th–Pb dating of monazite using electron microprobe analysis yielded a c . 200 Ma age for the older cores with low Th, Y, U and high La/Nd ratio, and a c . 160 Ma age for the dominant younger monazite enriched in Th, Y, U and HREE. The older age of c . 200 Ma is interpreted as the timing of UHPM, whereas the younger age of c . 160 Ma as granulite facies/partial melting overprint. Our results suggest that UHPM occurred in Late Triassic to Early Jurassic time, in the framework of collision and subduction of continental crust after the closure of Paleotethys.